Poisonings by pesticides: Impacts caused by indiscriminate use in rural communities (Research, Society and Development, 2021)
Objective: To analyze the impacts caused by the indiscriminate use of pesticides in rural communities. Methodology: Systematic review carried out through searches, between February and May 2021, in EMBASE, MEDLINE/PubMed, LILACS, CINAHL and PsycINFO databases. Results: With the completion of the search, 4,593 articles were found. Thus, 120 duplicates were removed and 2,644 for not being from the last 10 years, resulting in 1,829 articles for the evaluation of the other inclusion criteria by reading the titles and abstracts. After eligibility assessment, 762 articles presented potential for inclusion in the final study sample and, among these, 6 were selected for the final sample after a complete reading. It is noticed that the impacts are mainly aimed at the health of farmers and people who are close to them, regardless of whether or not they are directly involved in the handling of agrochemicals. However, it is noted that the main problem is centered on the lack of education of these workers in order to understand about the handling, protection and use and also of local health professionals, who are not able to carry out such activities. Conclusion: The main impacts that the indiscriminate use of pesticides causes for the population of rural workers are centered on damage to health, mainly mental. Still, it was identified that people who are close to these workers, such as family members who work or live directly or indirectly, are also exposed to suffering such damages, showing that the lack of information is a major factor for the worsening of cases.